Characterization of the chemical and antimicrobial properties of piscicolin 126, a bacteriocin produced by Carnobacterium piscicola JG126. - Jack, R W (1996)
A novel peptide bacteriocin produced by the lactic acid bacterium Carnobacterium piscicola JG126 isolated from spoiled ham was purified and characterized. This bacteriocin, designated piscicolin 126, inhibited the growth of several gram-positive bacteria, especially the food-borne pathogen Listeria monocytogenes, but had no effect on the growth of a number of yeasts and gram-negative bacteria. Bactericidal activity was not destroyed by exposure to elevated temperatures at low pH values; however, bactericidal activity was lost at high pH values, especially when high pH values were combined with an elevated temperature. Piscicolin 126 activity was not affected by catalase, lipase, or lysozyme but was destroyed by exposure to a range of proteolytic enzymes. Piscicolin 126 was purified to homogeneity and was found to be a peptide having a molecular weight of 4,416.6 +/- 1.9. A sequence analysis revealed that this compound is a cystibiotic (class IIa) bacteriocin containing 44 amino acid residues and one intrapeptide disulfide ring. Piscicolin 126 has regions of homology with some other bacteriocins obtained from lactic acid bacteria and is most closely related to sakacin P and pediocin PA-1 (levels of identity, 75 and 55%, respectively). Addition of piscicolin 126 to a devilled ham paste test food system inhibited the growth of L. monocytogenes for at least 14 days. Piscicolin 126 was more effective than two commercially available bacteriocin preparations tested in the same system.